2001
DOI: 10.1088/0953-8984/13/48/102
|View full text |Cite
|
Sign up to set email alerts
|

Structure and the location of the morphotropic phase boundary region in (1-x)[Pb(Mg1/3Nb2/3)O3]-xPbTiO3

Abstract: The structure of (1-x)[Pb(Mg1/3Nb2/3)O3]-xPbTiO3 is tetragonal and rhombohedral for x⩾0.35 and x⩽0.30, respectively. The intrinsic width of the morphotropic phase boundary region (0.30

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 24 publications
(23 reference statements)
8
88
1
Order By: Relevance
“…Instead of a line, a boundary, a morphotropic phase region was established circa 2000. This region is characterized by monoclinic symmetries: Cm [10][11][12][13], Cc [14,15], and Pm [16,17], either alone or coexisting with the neighboring rhombohedral and tetragonal symmetries. These monoclinic phases are considered to act as a structural bridge between the rhombohedral and tetragonal sides of the phase diagram, enabling the rotation of the polarization within the monoclinic plane [18][19][20].…”
Section: Temperature-composition Phase Diagrammentioning
confidence: 99%
“…Instead of a line, a boundary, a morphotropic phase region was established circa 2000. This region is characterized by monoclinic symmetries: Cm [10][11][12][13], Cc [14,15], and Pm [16,17], either alone or coexisting with the neighboring rhombohedral and tetragonal symmetries. These monoclinic phases are considered to act as a structural bridge between the rhombohedral and tetragonal sides of the phase diagram, enabling the rotation of the polarization within the monoclinic plane [18][19][20].…”
Section: Temperature-composition Phase Diagrammentioning
confidence: 99%
“…According to the X-ray diffraction the high temperature symmetry is cubic with the Pm3m space group [9][10][11][12][13][14][15][16][17][18]. As we already mentioned for such symmetry the first order Raman activity is forbidden.…”
Section: Temperature Evolution Of the Fwhms And Intensitiesmentioning
confidence: 99%
“…It must be stressed that the excellent electromechanical properties and the giant piezoeffect are A c c e p t e d m a n u s c r i p t 4 observed for the solid solutions with compositions belonging to the MPB. In general, these materials posses already ferroelectric behaviour and undergo the monoclinic (Pm) -> tetragonal (P4mm) -> cubic (Pm3m) structural phase transitions [11,12]. However, many authors [11,[13][14][15][16][17] suggested that the symmetry observed in the vicinity of the MPB is more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Recent extensive experimental investigations have discovered new intermediate phases and revealed fascinating while puzzling phase behaviors around the MPBs. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Since the recent discovery of an intermediate monoclinic M A phase in PZT near its MPB, [23][24][25][26][27][28] new intermediate phases have also been discovered in PZN-xPT and PMN-xPT near their respective MPBs, namely, monoclinic M A , [8][9][10] monoclinic M C , [8][9][10][11][12] orthorhombic ͑Refs. 8 and 13-15͒ phases in PZN-xPT, and orthorhombic, 16,17 monoclinic M C , 12,[18][19][20][21] monoclinic M A , 21,22 as well as a third monoclinic M B phase ͑Refs.…”
Section: Introductionmentioning
confidence: 99%
“…The recently established temperature-composition phase diagrams 15,19 and electric-field-temperature phase diagrams 10,21 reveal some fundamental aspects of the phase stabilities in the vicinity of MPBs. The large body of reported experimental data [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] provides information to investigate the relations between the phases and to clarify the origin of the ultrahigh electromechanical properties of these materials.…”
Section: Introductionmentioning
confidence: 99%